Analisis Pengaruh Persepsi Konsumen Mengenai Asal Negara, Persepsi Kualitas Dan Kualitas pelayanan Terhadap Minat Beli Mobil Honda Jazz di Kota Semarang - Jati Nugroho (Journal of Management, Entrepreneur and Cooperative, 2024)
This study aims to examine the influence of consumer perceptions regarding the origin of the country, the perception of quality and quality of service to the buying interest of Honda Jazz in Semarang City. The population in this study are car users in Semarang City. The number of samples used in this study is 120 respondents, it is eligible to be able to use ML as an estimation model. Sample technique in this study using accidental sampling where the authors find respondents encountered in crowded places such as malls or public places in Semarang using Honda Jazz. Analysis of data used is using SEM (Structural Equational Model) which based on the results showed. Country of Origin proved to have a positive and significant impact on Brand Image. Perceived Quality proved to have a positive and significant impact on Brand Image. Service Quality proved to have a positive and significant impact on Brand Image. Brand Image proved to have a positive and significant impact on Purchase Intention.